Estimating Truck Trip Generation for Airport Air Cargo Activity - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Airport Cooperative Research Program (ACRP) Synthesis 80: Estimating Truck Trip Generation for Airport Air Cargo Activity compiles existing information about air cargo truck trip generation studies. The existing literature and research regarding air cargo facility-related truck trip generation rates is limited in its scope and detail. In addition, the complexity of the modern air cargo industry makes it difficult to obtain the data necessary to develop truck trip generation rates. Access to such information could conceivably help a community plan and invest appropriately by accounting for air cargo’s impacts. Similarly, air cargo operators and airport officials could employ such data to help ensure cargo facility truck access and egress remains reliable and safe.
Keywords: Transportation and Infrastructure

Refining the Concept of Scientific Inference When Working with Big Data: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The concept of utilizing big data to enable scientific discovery has generated tremendous excitement and investment from both private and public sectors over the past decade, and expectations continue to grow. Using big data analytics to identify complex patterns hidden inside volumes of data that have never been combined could accelerate the rate of scientific discovery and lead to the development of beneficial technologies and products. However, producing actionable scientific knowledge from such large, complex data sets requires statistical models that produce reliable inferences (NRC, 2013). Without careful consideration of the suitability of both available data and the statistical models applied, analysis of big data may result in misleading correlations and false discoveries, which can potentially undermine confidence in scientific research if the results are not reproducible. In June 2016 the National Academies of Sciences, Engineering, and Medicine convened a workshop to examine critical challenges and opportunities in performing scientific inference reliably when working with big data. Participants explored new methodologic developments that hold significant promise and potential research program areas for the future. This publication summarizes the presentations and discussions from the workshop.
Keywords: Math, Chemistry, and Physics; Engineering and Technology; Policy for Science and Technology; Surveys and Statistics

Alternate Design/Alternate Bid Process for Pavement-Type Selection - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 499: Alternate Design/Alternate Bid Process for Pavement-Type Selection documents the state of the practice in alternate design/alternate bid (ADAB) for pavement-type selection by highway agencies. ADAB is a contracting technique that allows the pavement-type selection decision to be made as part of the procurement process. Contractors are permitted to bid their preferred pavement-type alternative using real-time market pricing for the paving materials.
Keywords: Transportation and Infrastructure

Cryptographic Agility and Interoperability: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
In May 2016, the National Academies of Sciences, Engineering, and Medicine hosted a workshop on Cryptographic Agility and Interoperability. Speakers at the workshop discussed the history and practice of cryptography, its current challenges, and its future possibilities. This publication summarizes the presentations and discussions from the workshop.
Keywords: Computers and Information Technology

Dispersion Modeling Guidance for Airports Addressing Local Air Quality Health Concerns - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Airport Cooperative Research Program (ACRP) Research Report 179: Dispersion Modeling Guidance for Airports Addressing Local Air Quality Health Concerns provides guidance for selecting and applying dispersion models to study local air quality health impacts resulting from airport-related emissions. The report explores challenges associated with modeling emissions in an airport setting for the purpose of understanding their potential impacts on human health.
Keywords: Transportation and Infrastructure

Demographic Effects of Girls' Education in Developing Countries: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Educating girls is a universally accepted strategy for improving lives and advancing development. Girls’ schooling is associated with many demographic outcomes, including later age at marriage or union formation, lower fertility, and better child health. However, the causal pathways between education and demographic outcomes are not well understood. To advance understanding of the relationships between girls’ education and demographic outcomes and to encourage more research on the determinants, content, context, and consequences of girls’ education the National Academies of Sciences, Engineering, and Medicine conducted a workshop addressing these issues on May 11 and 12, 2017. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Education; Behavioral and Social Sciences

Forum sur l'Investissement dans les Jeunes Enfants à l'Échelle Mondiale: Synthèse de neuf ateliers mondiaux Exploration fondée sur les faits des investissements stratégiques dans les jeunes enfants - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Focusing on young children in a global context is an approach to end the cycle of poverty and improve the well-being of nations. Improving well-being necessarily begins with core elements such as health, education, nutrition, and social protection; many efforts to improve child development in the first decade of life focus on areas to meet young children's basic needs. Young children living in low-resourced settings are vulnerable to developmental and educational risk factors, such as stunting and undernutrition, disease, caregiver depression, lack of access to quality preprimary and primary education, disabilities, poverty, and societal and familial violence. While each of these areas is important for children's growth and development, there are potential increased benefits from integrated programs and coordinated policies that address more than one of these areas simultaneously, particularly for children living in low-resourced communities. An integrated and coordinated "all system" approach may be the best way to guarantee that children will have the prerequisites for healthy development. The Forum on Investing in Young Children Globally was established with the goal of integrating knowledge with action in regions around the world to inform evidence-based, strategic investments in young children, birth through age 8. The forum held nine workshops across five continents over 3 years. The goal was to learn from experiences in multiple regions and engage in culturally embedded dialogue. This publication summarizes the key themes from the presentations and discussions of the workshops.
Keywords: Behavioral and Social Sciences; Health and Medicine

Integrating the Patient and Caregiver Voice into Serious Illness Care: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Millions of people—infants, children, adults, and their families—are currently coping with serious illness in the United States. Efforts are intensifying to improve overall care quality through the delivery of person-centered and family-oriented services, for patients of all ages and across disease stages, care settings, and specialties. While aging Baby Boomers are increasing the proportion of patients in the Medicare population over time, the sickest and most vulnerable patients needing health system support and other services to meet their complex needs can be found across the age spectrum and in a broad range of care settings, from perinatal care to geriatric care. Recognizing the need to thoughtfully consider and address the challenges and opportunities in efforts to improve care quality and value, the Roundtable on Quality Care for People with Serious Illness of the National Academies of Sciences, Engineering, and Medicine held the public workshop Integrating the Patient and Caregiver Voice into Serious Illness Care, on December 15, 2016, in Washington, DC. This workshop was the first in a series planned by the roundtable, and was designed specifically to bring together diverse personal perspectives and experiences about priorities and values that are important to patients and families coping with serious illness, and to consider solutions that support integration of these priorities and values in practice. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

An Evidence Framework for Genetic Testing - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Advances in genetics and genomics are transforming medical practice, resulting in a dramatic growth of genetic testing in the health care system. The rapid development of new technologies, however, has also brought challenges, including the need for rigorous evaluation of the validity and utility of genetic tests, questions regarding the best ways to incorporate them into medical practice, and how to weigh their cost against potential short- and long-term benefits. As the availability of genetic tests increases so do concerns about the achievement of meaningful improvements in clinical outcomes, costs of testing, and the potential for accentuating medical care inequality. Given the rapid pace in the development of genetic tests and new testing technologies, An Evidence Framework for Genetic Testing seeks to advance the development of an adequate evidence base for genetic tests to improve patient care and treatment. Additionally, this report recommends a framework for decision-making regarding the use of genetic tests in clinical care.
Keywords: Health and Medicine

Cancer Care in Low-Resource Areas: Cancer Treatment, Palliative Care, and Survivorship Care: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Though cancer was once considered to be a problem primarily in wealthy nations, low- and middle-income countries now bear a majority share of the global cancer burden, and cancer often surpasses the burden of infectious diseases in these countries. Effective low-cost cancer control options are available for some malignancies, with the World Health Organization estimating that these interventions could facilitate the prevention of approximately one-third of cancer deaths worldwide. Effective cancer treatment approaches are also available and can reduce the morbidity and mortality due to cancer in low-resource areas. But these interventions remain inaccessible for many people in the world, especially those residing in low-resource communities that are characterized by a lack of funds—on an individual or a societal basis—to cover health infrastructure and care costs. As a result, worse outcomes for patients with cancer are more common in low- and middle-income countries compared with high-income countries. Few guidelines and strategies for cancer control consider the appropriateness and feasibility of interventions in low-resource settings, and this may undermine the effectiveness of care. Recognizing the challenges of providing cancer care in resource constrained settings, the National Academies of Sciences, Engineering, and Medicine developed a two- workshop series examining cancer care in low-resource communities, building on prior work of the National Academies. The first workshop, held in October 2015, focused on cancer prevention and early detection. The second workshop was held in November 2016, and focused on cancer treatment, palliative care, and survivorship care in low-resource areas. This publication summarizes the presentations and discussions of this workshop.
Keywords: Health and Medicine

Implementation of Lung Cancer Screening: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The public health burden from lung cancer is substantial: it is the second most commonly diagnosed cancer and the leading cause of cancer-related deaths in the United States. Given the individual and population health burden of lung cancer, especially when it is diagnosed at later stages, there has been a push to develop and implement screening strategies for early detection. However, many factors need to be considered for broad implementation of lung cancer screening in clinical practice. Effective implementation will entail understanding the balance of potential benefits and harms of lung cancer screening, defining and reaching eligible populations, addressing health disparities, and many more considerations. In recognition of the substantial challenges to developing effective lung cancer screening programs in clinical practice, the National Academies of Sciences, Engineering, and Medicine held a workshop in June 2016. At the workshop, experts described the current evidence base for lung cancer screening, the current challenges of implementation, and opportunities to overcome them. Workshop participants also explored capacity and access issues; best practices for screening programs; assessment of patient outcomes, quality, and value in lung cancer screening; and research needs that could improve implementation efforts. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

The Promise of Assistive Technology to Enhance Activity and Work Participation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The U.S. Census Bureau has reported that 56.7 million Americans had some type of disability in 2010, which represents 18.7 percent of the civilian noninstitutionalized population included in the 2010 Survey of Income and Program Participation. The U.S. Social Security Administration (SSA) provides disability benefits through the Social Security Disability Insurance (SSDI) program and the Supplemental Security Income (SSI) program. As of December 2015, approximately 11 million individuals were SSDI beneficiaries, and about 8 million were SSI beneficiaries. SSA currently considers assistive devices in the nonmedical and medical areas of its program guidelines. During determinations of substantial gainful activity and income eligibility for SSI benefits, the reasonable cost of items, devices, or services applicants need to enable them to work with their impairment is subtracted from eligible earnings, even if those items or services are used for activities of daily living in addition to work. In addition, SSA considers assistive devices in its medical disability determination process and assessment of work capacity. The Promise of Assistive Technology to Enhance Activity and Work Participation provides an analysis of selected assistive products and technologies, including wheeled and seated mobility devices, upper-extremity prostheses, and products and technologies selected by the committee that pertain to hearing and to communication and speech in adults.
Keywords: Health and Medicine

Microbiomes of the Built Environment: A Research Agenda for Indoor Microbiology, Human Health, and Buildings - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
People's desire to understand the environments in which they live is a natural one. People spend most of their time in spaces and structures designed, built, and managed by humans, and it is estimated that people in developed countries now spend 90 percent of their lives indoors. As people move from homes to workplaces, traveling in cars and on transit systems, microorganisms are continually with and around them. The human-associated microbes that are shed, along with the human behaviors that affect their transport and removal, make significant contributions to the diversity of the indoor microbiome. The characteristics of "healthy" indoor environments cannot yet be defined, nor do microbial, clinical, and building researchers yet understand how to modify features of indoor environments—such as building ventilation systems and the chemistry of building materials—in ways that would have predictable impacts on microbial communities to promote health and prevent disease. The factors that affect the environments within buildings, the ways in which building characteristics influence the composition and function of indoor microbial communities, and the ways in which these microbial communities relate to human health and well-being are extraordinarily complex and can be explored only as a dynamic, interconnected ecosystem by engaging the fields of microbial biology and ecology, chemistry, building science, and human physiology. This report reviews what is known about the intersection of these disciplines, and how new tools may facilitate advances in understanding the ecosystem of built environments, indoor microbiomes, and effects on human health and well-being. It offers a research agenda to generate the information needed so that stakeholders with an interest in understanding the impacts of built environments will be able to make more informed decisions.
Keywords: Biology and Life Sciences; Engineering and Technology

Review of NASA's Evidence Reports on Human Health Risks: 2016 Letter Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
This is the fourth in a series of five letter reports that provide an independent review of the more than 30 evidence reports that NASA has compiled on human health risks for long-duration and exploration spaceflights.This letter report reviews eight evidence reports and examines the quality of the evidence, analysis, and overall construction of each report; identifies existing gaps in report content; and provides suggestions for additional sources of expert input.
Keywords: Health and Medicine; Space and Aeronautics

Accounting for Social Risk Factors in Medicare Payment - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Recent health care payment reforms aim to improve the alignment of Medicare payment strategies with goals to improve the quality of care provided, patient experiences with health care, and health outcomes, while also controlling costs. These efforts move Medicare away from the volume-based payment of traditional fee-for-service models and toward value-based purchasing, in which cost control is an explicit goal in addition to clinical and quality goals. Specific payment strategies include pay-for-performance and other quality incentive programs that tie financial rewards and sanctions to the quality and efficiency of care provided and accountable care organizations in which health care providers are held accountable for both the quality and cost of the care they deliver. Accounting For Social Risk Factors in Medicare Payment is the fifth and final report in a series of brief reports that aim to inform ASPE analyses that account for social risk factors in Medicare payment programs mandated through the IMPACT Act. This report aims to put the entire series in context and offers additional thoughts about how to best consider the various methods for accounting for social risk factors, as well as next steps.
Keywords: Health and Medicine

Review of WIC Food Packages: Improving Balance and Choice: Final Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) began 40 years ago as a pilot program and has since grown to serve over 8 million pregnant women, and mothers of and their infants and young children. Today the program serves more than a quarter of the pregnant women and half of the infants in the United States, at an annual cost of about $6.2 billion. Through its contribution to the nutritional needs of pregnant, breastfeeding, and post-partum women; infants; and children under 5 years of age; this federally supported nutrition assistance program is integral to meeting national nutrition policy goals for a significant portion of the U.S. population. To assure the continued success of the WIC, Congress mandated that the Food and Nutrition Service of the U.S. Department of Agriculture (USDA) reevaluate the program's food packages every 10 years. In 2014, the USDA asked the Institute of Medicine to undertake this reevaluation to ensure continued alignment with the goals of the Dietary Guidelines for Americans. In this third report, the committee provides its final analyses, recommendations, and the supporting rationale.
Keywords: Food and Nutrition

Strategies to Limit Sugar-Sweetened Beverage Consumption in Young Children: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On June 21–22, 2017, the National Academies of Sciences, Engineering, and Medicine's Food and Nutrition Board convened a workshop in Washington, DC, to explore the range of policies and programs that exist at the federal, state, tribal, and local levels to limit sugar-sweetened beverage consumption in children birth to 5 years of age. Topics examined over the course of the 1.5-day workshop included prevalence and trends in beverage intake among young children; beverage intake guidelines applicable to the age range of interest; challenges and opportunities of influencing beverage consumption; the role of industry in beverage intake; and knowledge gaps and research needs. This publication summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition

Additional Observations on Foundational Cybersecurity Research: Improving Science, Engineering, and Institutions: An Annex: Unclassified Abbreviated Version of a Classified Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
At the request of the Special Cyber Operations Research and Engineering (SCORE) Interagency Working Group and sponsored with assistance from the National Science Foundation and from the Office of the Director of National Intelligence, the National Academies of Sciences, Engineering, and Medicine appointed an expert committee to explore future research goals and directions for cybersecurity. The committee for this multi-phased sequential study considered future research goals and directions for foundational science in cybersecurity, and included relevant efforts in economics and behavioral science as well as more “traditional” cybersecurity topics. It considered major challenge problems, explored proposed new directions, identified gaps in the current portfolio, considered the complementary roles of research in unclassified and classified settings, and considered how foundational work in an unclassified setting can be translated to meet national security objectives. This abbreviated annex provides background information on the full classified annex resulting from the study.
Keywords: Computers and Information Technology; Conflict and Security Issues

Strategies to Limit Sugar-Sweetened Beverage Consumption in Young Children: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On June 21–22, 2017, the National Academies of Sciences, Engineering, and Medicine’s Food and Nutrition Board convened a workshop in Washington, DC, to explore the range of policies and programs that exist at the federal, state, tribal, and local levels to limit sugar-sweetened beverage consumption in children birth to 5 years of age. Topics examined over the course of the 1.5-day workshop included prevalence and trends in beverage intake among young children; beverage intake guidelines applicable to the age range of interest; challenges and opportunities of influencing beverage consumption; the role of industry in beverage intake; and knowledge gaps and research needs. This publication highlights key points made by individual speakers during the presentations and discussions.
Keywords: Food and Nutrition; Health and Medicine

Driving Action and Progress on Obesity Prevention and Treatment: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The Roundtable on Obesity Solutions of the Health and Medicine Division of the National Academies of Sciences, Engineering, and Medicine held a workshop in Washington, DC, on September 27, 2016, titled "Driving Action and Progress on Obesity Prevention and Treatment." The workshop was designed to (1) review the progress that has been made in obesity prevention and treatment; (2) identify some of the levers that can drive significant future progress; and (3) discuss how gaps in the field can be filled. This Proceedings of a Workshop-in Brief highlights key points made during the presentations and discussions and is not intended to provide a comprehensive summary of information shared during the workshop.
Keywords: Food and Nutrition